Study of Mudharabah Literature in Banking in Indonesia - Harahap, Haddad ’Ulum; Harahap, Rijal Allamah (ITB AAS INDONESIA Surakarta, 2023)
This literature aims to determine the mudharabah in banking in Indonesia. The results of the literature show that Murabahah is considered one of the products that is widely criticized by academics because in this scheme, there is no risk sharing between banks and customers. The absence of risk on the side of Islamic banking causes the risk to be fully borne by the customer, while Islamic banks are relatively safe from risk. The Mudharabah system is actually a promising alternative when compared to the interest system. This is because in the mudharabah system there is a principle of justice in it by positioning the owners of capital (rabb al mal) and entrepreneurs (mudharib) as partners. On the liability side, mudharabah is applied to: Time savings, ordinary deposits and special deposits, while on the asset side, mudharabah is set at: Working capital financing and special investments.